Cognitive Load and Occupational Injuries. Issue 2 (13th April 2021) - Bonsang, Eric; Caroli, Eve
Abstract : We investigate the relationship between cognitive load and occupational injuries. Cognitive load is defined in the literature as a tax on bandwidth which reduces cognitive resources. We proxy cognitive load with the number of nonprofessional tasks that individuals perform during weekdays. The underlying assumption is that when individuals perform many of those tasks, this requires mental organization which reduces available cognitive resources. We show that being cognitively loaded is associated with an increase in the risk of occupational injury for both males and females. The effect is stronger for individuals in high‐risk occupations and, among those, for low‐educated workers.